Correlation of TyG-BMI and TyG-WC with severity and short-term outcome in new-onset acute ischemic stroke - Yu, Xin-Rui; Du, Jing-Lu; Jiang, Mei; Ren, Yuan; Zhang, Fu-Liang; Kong, Fan-Li; Li, Feng-E. (Frontiers in Endocrinology, 2024)
Objective: To research the connection between the indexes of the indexes of triglyceride-glucose (TyG) combined with obesity indices and the initial neurological severity and short-term outcome of newonset acute ischemic stroke.Methods: Data of patients with acute ischemic stroke admitted to the Stroke Ward of the Affiliated Hospital of Beihua University from December 1, 2020, to December 31, 2022, were collected. The two indexes were calculated by combining TyG and obesity indices: TyG-body mass index (TyG-BMI) and TyG-waist circumference (TyG-WC). The National Institute of Health Stroke Scale (NIHSS) was used to assess and group patients with neurological deficits within 24 hours of admission: mild stroke (NIHSS ≤5) and moderate-severe stroke (NIHSS >5). Short-term prognosis was evaluated using the modified Rankin Scale (mRS) at discharge or 14 days after onset of the disease and grouped: good outcome (mRS ≤2) and poor outcome (mRS >2). According to the quartiles of TyG-BMI and TyG-WC, the patients were placed into four groups: Q1, Q2, Q3 and Q4. Multi-factor logistic regression analysis was utilized to evaluate the correlation of TyG-BMI and TyG-WC with the severity and short-term outcome.The study included 456 patients. After adjusting for multiple variables, the results showed that compared with the quartile 1, patients in quartile 4 of TyG-BMI had a reduced risk of moderatesevere stroke [Q4: OR: 0.407, 95%CI (0.185-0.894), P = 0.025]; Patients in quartiles 2, 3 and 4 of TyG-BMI had sequentially lower risk of short-term adverse outcomes [Q2: OR: 0.394, 95%CI (0.215-0.722), P = 0.003; Q3: OR: 0.324, 95%CI (0.163-0.642), P = 0.001; Q4: OR: 0.158, 95%CI (0.027-0.349), P <0.001]; Patients in quartiles 3 and 4 of TyG-WC had sequentially lower risk of moderate-severe stroke [Q3: OR: 0.355, 95%CI (0.173-0.728), P = 0.005; Q4: OR: 0.140, 95%CI (0.056-0.351), P <0.001]; Patients in quartiles 3 and 4 of TyG-WC had sequentially lower risk of short-term adverse outcomes [Q3: OR: 0.350, 95%CI (0.175-0.700), P = 0.003; Q4: OR: 0.178, 95%CI (0.071-0.451), P <0.001].TyG-WC and TyG-BMI were correlated with the severity and short-term outcome of new-onset acute ischemic stroke. As TyG-WC and TyG-BMI increased, stroke severity decreased and short-term outcome was better.